Student Behavior In Utilization Internet Of Library Based On Information - Aprih Santoso (Jurnal Visi Manajemen, 2021)
The research objective is to examine the effect of social factors on intention and their impact on student behavior in utilization internet of library as an information media. The method used is the survey method by distributing questionnaires. The research data obtained is based on the perception student of Universitas Semarang students on the utilization internet of library carried out by the Universitas Semarang Library as a student information media, with 95 respondents. The research method uses validity test, reliability test, and classic assumption test, hypothesis test, multiple linear regression model (path analysis) with SPSS 23 program. The results of testing social factors directly and indirectly through the intention in using internet of library do not effect on student behavior in utilization internet of library carried out by Universitas Semarang students as their information media.